Investigation of the monopole magneto-chemical potential in spin ices using capacitive torque magnetometry - Naween Anand; Kevin Barry; Jennifer N. Neu; David E. Graf; Qing Huang; Haidong Zhou; Theo Siegrist; Hitesh J. Changlani; Christianne Beekman (Nature Communications, 2022)
Magnetic-field induced phase transitions in spin-ice materials have been investigated with various experimental techniques. Here, the authors demonstrate the capability of capacitive torque magnetometry in probing magnetic interaction energies and establishing magnetic phase boundaries in Ho2Ti2O7.